2016
DOI: 10.1155/2016/6756983
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Mesenchymal Stem‐Like Cell as a Prognostic Marker in Primary Glioblastoma

Abstract: The isolation from brain tumors of tumor mesenchymal stem-like cells (tMSLCs) suggests that these cells play a role in creating a microenvironment for tumor initiation and progression. The clinical characteristics of patients with primary glioblastoma (pGBM) positive for tMSLCs have not been determined. This study analyzed samples from 82 patients with pGBM who had undergone tumor removal, pathological diagnosis, and isolation of tMSLC from April 2009 to October 2014. Survival, extent of resection, molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 43 publications
1
23
0
Order By: Relevance
“…Other studies isolated MSC-like cells from GB and these cells were shown to increase angiogenesis, and GB cell proliferation and invasion [ 54 58 ]. Consistent with these findings, it has been recently observed that the percentage of GB-associated MSC-like cells is inversely correlated with overall survival, indicating a role for these cells in promoting the aggressive behavior of GB [ 59 , 60 ]. All these data raise the question if MSCs are interesting candidates as cellular vehicles for the delivery of a therapeutic molecule in a GB context.…”
Section: Discussionsupporting
confidence: 70%
“…Other studies isolated MSC-like cells from GB and these cells were shown to increase angiogenesis, and GB cell proliferation and invasion [ 54 58 ]. Consistent with these findings, it has been recently observed that the percentage of GB-associated MSC-like cells is inversely correlated with overall survival, indicating a role for these cells in promoting the aggressive behavior of GB [ 59 , 60 ]. All these data raise the question if MSCs are interesting candidates as cellular vehicles for the delivery of a therapeutic molecule in a GB context.…”
Section: Discussionsupporting
confidence: 70%
“…In line with this trend, tMSLCs are recently defined as stromal cells interacting with GBM cells and their potential role in tumor progression has received intensive attention [11, 12, 2325]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, tMSLCs have been reported as stromal cells interacting with GBM cells, and their potential role in tumor progression has received intensive attention ( 27 , 28 ). However, it remains controversial whether tMSLCs in the tumor microenvironment play a role in cancer promotion or suppression ( 29 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…These contrasting results could be caused by differences in their origin and/or the type of tumor. Thus, we previously isolated tMSLCs directly from human GBM surgical specimens and found that their presence is closely correlated with the prognosis of patients ( 28 ). In this current study, we provide another strong evidence that tMSLCs act as stromal cells promoting GBM progression by force-mediated proinvasive ECM remodeling.…”
Section: Discussionmentioning
confidence: 99%